Impact of postoperative flurbiprofen axetil on renal function in spontaneously hypertensive rats - Sun, Liang; Ma, Xiaoran; Jiang, Yuhui; Zhang, Wanda; Feng, Yi (Frontiers in Pharmacology, 2025)
BackgroundFlurbiprofen axetil (FA) is a nonsteroidal anti-inflammatory drug frequently used in postoperative analgesia. However, limited data exist regarding its impact on renal profiles. Here we determine the potential impact of postoperative FA on renal function in spontaneously hypertensive (SH) rats.MethodsA plantar incision model was established to mimic post-surgical pain in SH rats. Animals were randomly assigned to groups called vehicle (fat emulsion, 0.5 mL/d), low-dose FA (H12.5, 12.5 mg/kg/d), medium-dose FA (H25, 25 mg/kg/d) or high-dose FA (H50, 50 mg/kg/d). Analogously, 40 male Wistar Kyoto (WKY) rats were included as controls in groups called vehicle, C12.5, C25, and C50. The vehicle and different doses of FA were administered from the day of surgery through postoperative day 2 (POD2). Paw withdrawal thresholds (PWTs) were measured before and after incision. Urinary N-acetyl-β-D-glucosaminidase (NAG), serum creatinine (SCr), and Cystatin C (Cys C) were measured. Animals were sacrificed for renal pathology analysis on POD7.ResultsPWTs exhibited a dose-dependent increase after postoperative administration of FA on POD1 and POD2, but with a ceiling effect at the medium dose in both SH and WKY rats. Compared with the vehicle group, the levels of SCr in the C50, H25, and H50 groups were significantly increased on POD2 and POD7 (all P < 0.01). The concentration of Cys C in C12.5, C25, and C50 groups, as well as H12.5, H25, and H50 groups on POD2, were increased in a dose-dependent manner (all P < 0.05), similar trend was detected in H25, and H50 groups on POD7. Urine NAG levels in the H12.5, H25 and H50 groups on POD2, as well as H25 and H50 groups on POD7 were elevated in comparison with the vehicle groups (all P < 0.05). Partial glomerular and tubular damage was found in the H25 group. Extensive renal impairments were observed in the C50 and H50 groups.ConclusionMedium-dose FA effectively alleviates postoperative pain and achieves a ceiling effect in SH rats. FA decreases glomerular and tubular function to a certain extent in both normo- and hypertensive rats. Renal impairment is detectable earlier after surgery in hypertensive rats, even at the lowest FA dose applied here.